Eine Kreisstadt zwischen den Welten - Hartmuth, Maximilian (Leykam Buchverlag, 2023)
The architecture of the Habsburg period left landmarks in the provincial capital Sarajevo. But this orientalizing ("Moorish") style also found expression in the provinces. More than other places, it left its mark on the central Bosnian town of Travnik. Its designation as the seat of the district administration, its connection to the railroad network and construction activity as a result of major fires ensured that the district office was bustling with activity. The central question of this study is the role played by architects and engineers in the service of the provincial administration and their superordinate decision-makers in the spread of this style and the consolidation of a repertoire of forms. How was cultural convergence administered? What forms did it take outside the metropolitan areas? And what about this "colonial" heritage today?